Effect of stacking sequence and porosity on creep behavior of glass/epoxy and carbon/epoxy hybrid laminate composites - Ornaghi, Heitor Luiz [UNESP] (2020)
The creep behavior of hybrid carbon/glass laminate composites was investigated using a dynamic mechanical analyzer and different temperature profiles. Dynamic analysis and porosity were carried out prior to the creep test applying Findley's power law. The dynamic curves were not influenced by porosity but were affected by the architecture of the composites. The creep tests showed porosity dependence at temperatures below Tg while at higher temperatures, the architecture of the reinforcement plays a major role. Time-temperature superposition was conducted for long-term creep prediction and the results showed lower creep strain for the carbon and interleaved hybrid composites.